APLIKASI NEAR INFRARED SPECTROSCOPY (NIRS) DALAM PENGUKURAN KEHILANGAN MINYAK DAN PENGUJIAN AKURASINYA DIBANDINGKAN DENGAN METODE SOKLET - Irfan, Irfan; Aji, Iqbal Fitri; Yunita, Dewi (Jurnal Agroindustri, 2023)
Loss of oil during crude palm oil (CPO) extraction occurs among other things, due to the use of high temperature and pressure in the boiling process so that the oil from the fruit is absorbed and remains in the empty fruit bunches (EFB). This oil loss is generally measured using Soxhlet method. However, recently in several palm oil mills (POM), the Soxhlet method has been replaced by the Near Infrared Spectroscopy (NIRS) method which is equipped with free and open-source software (FOSS). Therefore, the purpose of this study was to examine the application of NIRS in measuring oil loss in EFB and to test its accuracy compared to the Soxhlet method. The data is from primary source of POM during April-June 2022 period (peak harvest times). Normality test and paired T test is used to analyze data. This research also cites case studies of CPO processing companies in Indonesia in the last 10 years (2013-2022) with a focus on oil loss in EFB. The results showed that the oil loss in EFB using NIRS and Soxhlet were 0.50% and 0.49%, respectively. These two values are below the company's oil loss standard (0.62%). Both data are normally distributed and based on the paired T test, it was found that there were no significant differences in the results of oil loss analysis using the NIRS and Soxhlet methods. Compared with data for the last 10 years, they are also below the standard limit of other companies which reaches 3%. Therefore, NIRS is more recommended in terms of time efficiency, safe and does not damage the material.